Sistema para visualização do movimento da pele mediante reposicionamento ósseo por meio da cirurgia ortognática - Uebele, Daniela Teresa Rossignoli (2014)
It is highlighted the influence and use of Computer Graphics discipline, applied in different areas of health. Positive results have been reported by several studies mainly pointing reliability, which enables creation of new techniques in search of better results. The available literature for orthognathic surgery demonstrates the severe shortage of technologies in supporting surgeons and their patients. The number of patients using traditional braces and do not get satisfactory results is significantly large, leaving only the option of undergoing orthognathic surgery, which might involve the breaking of bones and soft tissue and muscles arrangements. Such procedure is indicated for patients who have very pronounced symptoms like problems in the relationship between the teeth, muscles and bones, face s muscles pain, tongue position and temporomandibular joint (TMJ). These problems may cause headaches and stomach disorders, besides respiration and phonation issues and apnea. This study describes the analysis and three-dimensional simulation in repositioning of the upper and lower jaws concerning soft tissue and skin, with the goal of assisting in a better surgical planning using CT scans efficiently, thus supporting doctor and patient in the submission of the surgical procedure. There is also the intention to include the software prototype created as part of this study in the InVesalius (TM) software adding support for orthognatic surgery procedure. A group of surgeons evaluated the software prototype presented in this study. The potential of this tool is discussed in this dissertation and its test results.